(untitled) (JURNAL HUKUM DAS SOLLEN, 2022)
Globalization is currently happening very rapidly, one of the causes is the development of technology and communication. With the conveniences obtained, someone can easily publish their copyright. These copyright can be viewed and enjoyed quickly, cheaply, and without limits. One of the factors is the development of social media such as Facebook, Twitter, Instagram, etc. For this reason, more progressive legal protection is needed in protecting the work of the creator so that his rights, both moral and economic, can be maintained. But unfortunately the development of social media is not directly proportional to copyright law so that there are many copyright infringement on social media which of course harms the creator and harms the Indonesian nation. This article will discuss: 1) What are the forms of copyright infringement that occur on social media? And 2) What are the legal problems in protecting copyright on social media. The method used is normative juridical. In this article, it can be seen that the forms of copyright infringement that occur on social media include illegal downloading, streaming, and streamripping. This action is called digital piracy, because it is carried out without permission from the creator or copyright owner and violates applicable laws and regulations. And the problem with copyright protection law on social media is that copyright protection is still territorial so that each country provides different settings and standards. In addition, there is a lack of public understanding of respect for other people’s creative works, as well as the communal characteristics of Indonesian society. Then it is complicated by the weakness of the rule of law and the inadequacy of laws that protect copyright, including copyrighted works that are announced through social media. Besides that, there is weak law enforcement and also the control of related agencies over copyrighted works.